Comparative Analysis of Pretreatment Methods for Processing Bulk Flax and Hemp Oilseeds Under Uniaxial Compression - Abraham Kabutey; Sonia Habtamu Kibret; Asmerom Woldemichael Kiros; Meseret Abraham Afework; Michael Onwuka; Akshay Raj (Foods)
The purpose of this study was to examine the effect of oven and vacuum pretreatment techniques at drying temperatures between 40 °C and 90 °C and a constant heating time of 60 min on the oil yield, energy output, and compressive stress of bulk flax and hemp oilseeds samples. The results showed that heating temperatures linearly increased the amounts of oil yield but did not correlate linearly with energy requirement. The oven pretreatment slightly increased the oil yield and energy compared to the vacuum pretreatment. Higher compressive stress values were observed for hemp oilseeds than flax oilseeds which could be attributed to the inherent structure of the oilseeds. Hemp oilseeds showed more toughness to compress than flax oilseeds which tend to have a softer texture. The lack-of-fit p-values > 0.05 of the linear regression models dependent on the heating temperature under both drying conditions indicate adequacy for predicting the calculated parameters. Tukey’s significance test showed that the means of oil yield and energy of bulk flax and hemp oilseeds under the oven and vacuum pretreatments revealed no significant difference implying that both pretreatment methods can initiate the same heat treatment effect on oil extraction efficiency with the corresponding energy requirement.